Android secure MMS application - Muhammad Wahidin Wahid. (2013)
Computer security has always been an integral subject among people. Ever since the first man who altered his transaction bank account by altering a few computer codes, there has been a significant rise in the crime of technology. Today, with the popularity of smartphones, it is even more important that we understand the security protecting our messages.